The Dialectical Conception of the Process of Development - Meškauskas, Eugenijus (Problemos, 1987)
The interrelation between the dialectical conception of the process of development and the methodological problems of modern science is analysed in the article. The methodological contents of the main laws of the process which are the expression of different aspects of the same object, are revealed.